2014
DOI: 10.1111/1440-1681.12309
|View full text |Cite
|
Sign up to set email alerts
|

Berberine attenuates adverse left ventricular remodeling and cardiac dysfunction after acute myocardial infarction in rats: Role of autophagy

Abstract: The present study aimed to test the hypothesis that berberine, a plant-derived anti-oxidant, attenuates adverse left ventricular remodelling and improves cardiac function in a rat model of myocardial infarction (MI). Furthermore, the potential mechanisms that mediated the cardioprotective actions of berberine, in particular the effect on autophagy, were also investigated. Acute MI was induced by ligating the left anterior descending coronary artery of Sprague-Dawley rats. Cardiac function was assessed by trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…Moreover, echocardiographic assessments showed that LVIDs, LVIDd, systolic volume, and diastolic volume of coronary artery-ligated rats receiving vehicle were significantly higher, while SV, EF, FS, and CO of that group were significantly lower than those of the sham-operated group. The echocardiographic findings are similar to those of earlier studies on experimental (Huang et al 2009;Mercanoglu et al 2010;Zhang et al 2014;Zhou et al 2007) and clinical (Radovanovic et al 2012) heart failure. Sham-V sham group receiving vehicle (1 ml distilled water/day), CAL-V coronary arteryligated group receiving vehicle (1 ml distilled water/day), CALOle-5 coronary artery-ligated group receiving oleuropein at 5 mg/kg/ day, CAL-Ole10 coronary arteryligated group receiving oleuropein at 10 mg/kg/day, CAL-Ole20 coronary artery-ligated group receiving oleuropein at 20 mg/kg/ day.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, echocardiographic assessments showed that LVIDs, LVIDd, systolic volume, and diastolic volume of coronary artery-ligated rats receiving vehicle were significantly higher, while SV, EF, FS, and CO of that group were significantly lower than those of the sham-operated group. The echocardiographic findings are similar to those of earlier studies on experimental (Huang et al 2009;Mercanoglu et al 2010;Zhang et al 2014;Zhou et al 2007) and clinical (Radovanovic et al 2012) heart failure. Sham-V sham group receiving vehicle (1 ml distilled water/day), CAL-V coronary arteryligated group receiving vehicle (1 ml distilled water/day), CALOle-5 coronary artery-ligated group receiving oleuropein at 5 mg/kg/ day, CAL-Ole10 coronary arteryligated group receiving oleuropein at 10 mg/kg/day, CAL-Ole20 coronary artery-ligated group receiving oleuropein at 20 mg/kg/ day.…”
Section: Discussionsupporting
confidence: 90%
“…Berberine is an important alkaloid derived from Coptis chinensis Franch (Huang Lian). Previous studies [10][11] indicated that berberine had cardioprotective effects that included lowering lipids, reducing ischemia/reperfusion-induced myocardial apoptosis, and attenuating adverse left ventricular remodeling [12][13][14] . Our previous study in rats with acute myocardial infarction [15] showed that combined ligustrazine and berberine produced more effective inhibition of platelet activation and inflammatory reactions than did either agent separately.…”
Section: Introductionmentioning
confidence: 99%
“…Berberine is a small fluorescent isoquinoline quaternary alkaloid which has proven to be useful at high doses as a cardio-protectant (Zhang et al 2014) and for improvement of cardiac function (Huang et al 2015). Berberine-loaded liposomes have been developed and tested for IL-6 secretion inhibition and cardiac function protection against adverse remodelling after MI in C57BL/6J mice (Allijn et al 2017).…”
Section: Liposomesmentioning
confidence: 99%